ETNOMATEMATIKA: EKSPLORASI ORNAMEN RUMAH BOLON BATAK TOBA TERHADAP KONSEP GEOMETRI - Susi Sihombing (STKIP Singkawang, 2021)
The purpose of this study was to explore the ornaments of the Toba Batak house on the concept of geometry. This type of research is qualitative based on ethnomathematics. The research was conducted at the Tobasa Regency Museum T.B Silalahi Center. Analysis of the data used is observation, interviews and documentation. Based on the results of the analysis, it is concluded that the Toba Batak House ornaments are related to the geometric concept, namely pentagons, circles, triangles, transformations, cones, reflections, rectangles, and squares.